(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
The problems of global warming and noise pollution require solutions aimed at reducing greenhouse gas emission carbon II oxide (CO) and automobile engine noise. To do this focus must be on measures that enhance the reduction of CO emission and engine noise in vehicle. One of such measures is the use of a gaseous fuel Compressed Natural Gas (CNG) for vehicular transportation. In this work, exhaust emission and engine noise of a vehicle fueled with CNG is compared with exhaust emission and engine noise of the same vehicle fueled with petrol. The exhaust emissions were measured using a portable CO meter and noise level was measured with a sound level meter. The test results show that compared to petrol, CNG allows for a significant decrease in CO emission and engine noise of an automobile vehicle engine.